Advanced separation of concerns in agent-oriented design patterns. (6th March 2009) - Silva, Carla; Castro, Jaelson; Araujo, Joao; Moreira, Ana; Tedesco, Patricia; Mylopoulos, John
Social patterns are agent-oriented design patterns that have been conceived to reflect the social and intentional features that are recurrent in cooperative and Multi-Agent Systems (MAS). The goal of this paper is to present a social pattern description technique called Agent Pattern Specification (APS), which takes into account the separation of pattern-related concerns in the MAS design level. We also use aspect-oriented programming to separate pattern-specific concerns in the MAS implementation level and evaluate it by using a suite of metrics for assessing well-known software engineering attributes such as the separation of concerns, coupling, cohesion and size. Our assessment suggests that the aspect-oriented solutions for mediation patterns improve the separation of pattern-related concerns.